Implementasi Akuntasi Sektor Publik Dalam Sistem Keuangan Pemerintah Desa Karangrejo Tahun 2020 - Arung Abinaya Nasrulloh ,; Zarah Eka Nur Saputri ,; Herlina Manurung , (Jurnal Mutiara Ilmu Akuntansi, 2023)
The implementation of public sector accounting is very important to ensure transparency, efficiency and effectiveness in the financial management of government entities, including village governments. This study explores the extent to which the Karangrejo Village Government has adopted and implemented public sector accounting standards, procedures, and reporting practices in its financial system. This research includes studies on accounting policies, budgeting processes, and the smaller number of financial transactions of village governments compared to local governments. The results of the study indicate that the policies implemented by the Karangrejo village government are in accordance with applicable regulations and have been evaluated by accountants in presenting accountability reports. In addition, the village government has prepared financial reports, including balance sheets, income statements, and cash flow statements, which provide comprehensive information on village financial activities and assist in assessing village financial performance and accountability. The preparation of financial reports using a village-based accounting information system (SISKEUDES) also assists village officials in compiling financial accounting reports for village funds more seriously. This study concludes that the implementation of public sector accounting in the Karangrejo Village Government financial system in 2020 has increased financial transparency, accountability, and governance. However, there is still room for improvement, such as strengthening internal controls, increasing capacity building programs for village officials, and ensuring the sustainability of accounting practices that have been implemented.